Public Health and Social Desirability in Kazakhstan: Methodological Considerations - Brett J. Craig; Martha C. Engstrom (University Library System, University of Pittsburgh, 2016)
Background: As the Republic of Kazakhstan undertakes new public health efforts to promote healthy lifestyles among its citizens, the local perceptions of health and health behaviors need to be examined and understood from the sociocultural and historical perspectives. The primary aim of this study is to examine the association between perception of control on one's health and engagement in good and bad health behaviors. Methods: Students enrolled in a health communication course surveyed 310 citizens of Kazakhstan on their perceptions of control over their own health and multiple health behaviors (i.e. smoking status, physical activity, etc.). Twenty-seven students were divided into groups and approached every third passerby as a potential participant during common shopping hours in nine popular marketplaces in Astana, Kazakhstan. Perception of control on one's health was measured using a validated measure of health control: the multidimensional health locus of control scale (MHLC), developed by Wallston and colleagues. The MHLC measures three separate loci of control: internal, chance, and powerful others. Results: Participants perceived themselves as having highest control over their health (MHLC subscale internal: 29.70±0.64), powerful others had second highest control (MHLC subscale power others: 23.72±0.77), and chance had the lowest but still some control on their health (MHLC subscale chance: 20.82±0.85). Most participants rated their current health as very good (18.1%), good (45.0%), or moderate (32.3%). Approximately 23.4% of participants were smokers, and 22.2% consumed alcohol. Physical activity averaged 3.63 days in the past week, and fruit and vegetable consumption averaged 2 servings of each per day.  Tobacco and the powerful others subscale were significantly negatively correlated (r=-0.17, p<0.05).  Conclusions: Participant reports regarding personal health behaviors and lifestyle did not reflect the national reports regarding lifestyle behaviors. The relationship between powerful others subscale and tobacco smoking indicate that using healthcare providers may open up avenues to lowering tobacco use through patient education; however, social desirability is a notable concern for public health interventions. More importantly, the surveys uncovered future questions for conducting public health research with the general public, including issues of trust in the healthcare system and social desirability bias. Additional factors such as distrust in healthcare and government also may play a role in the public's participation in social scientific research. The students who conducted the surveys reported a general skepticism from the public ranging from unfamiliarity with survey research to explicit distrust in the intentions and purpose of the research itself.